THE INFLUENCE OF VOCABULARY MASTERY TOWARD ENGLISH SPEAKING ABILITY OF THE FOURTH SEMESTER STUDENTS OF ENGLISH EDUCATION STUDY PROGRAM MUHAMMADIYAH UNIVERSITY - Yasmika Baihaqi (Premise: Journal of English Education and Applied Linguistics, 2014)
One of the purpose of teaching speaking is the students are able to use English as a means of communication based on the context and situation related to their level of vocabulary mastery. So before we are able to communicate well, we should have a large number of words.The objective of this research is to find out whether vocabulary is influential toward English speaking ability. The populations of this research are 190 students of all the fourth semester in the academic year of 2009-2010. Based on the table of Krecjie, a number of samples are 127 students. The sampling technique used is the simple random sampling technique. To collect the data, the researcher requires two tests, vocabulary and speaking tests.This study yields that there is a positive and significant influence between English vocabulary mastery and the students’ speaking ability, it is proved by the value of correlation coefficient 0.764 which is higher than the value of r table (0.176). It means that the rise of the independent variable (the students’ vocabulary mastery) will be followed by the rise of the dependent variable (English speaking ability). The effective contribution of the students’ vocabulary mastery toward English speaking ability is 58.6%